Advances in Research on the Toxicological Effects of Selenium - Lv, Qizhuang; Liang, Xiaomei; Nong, Keyi; Gong, Zifeng; Qin, Ting; Qin, Xinyun; Wang, Daobo; Zhu, Yulin (Bulletin of environmental contamination and toxicology, 2021)
Selenium is a trace element necessary for the growth of organisms. Moreover, selenium supplementation can improve the immunity and fertility of the body, as well as its ability to resist oxidation, tumors, heavy metals, and pathogenic microorganisms. However, owing to the duality of selenium, excessive selenium supplementation can cause certain toxic effects on the growth and development of the body and may even result in death in severe cases. At present, increasing attention is being paid to the development and utilization of selenium as a micronutrient, but its potential toxicity tends to be neglected. This study systematically reviews recent research on the toxicological effects of selenium, aiming to provide theoretical references for selenium toxicology-related research and theoretical support for the development of selenium-containing drugs, selenium-enriched dietary supplements, and selenium-enriched foods.